A Three-dimensional Analysis of Zygomatic Symmetry in Normal, Uninjured Faces. Issue 2 (March 2016) - Belcastro, Alexandra; Willing, Ryan; Jenkyn, Thomas; Johnson, Marjorie; Galil, Khadry; Yazdani, Arjang
Abstract : Abstract: Current approaches to facial reconstruction are based on the assumption of facial symmetry, though this has yet to be established in the literature. Through quantitative and qualitative analysis, symmetry of normal, male faces is examined here using the zygomatic complex as a bellwether for the rest of the facial skeleton. Three-dimensional models reconstructed from the computed tomography scans of 30 adult male patients displaying normal facial skeletal anatomy were analyzed. Seven zygomatic landmarks were identified on all craniofacial models, and asymmetry scores were calculated based on the average deviation distance upon reflection of 1 hemiface across the midfacial plane. Deviation maps were then generated for each zygomatic pair to enable visualization of the asymmetry. All landmarks displayed a slight (<3 mm) deviation from perfect symmetry, and analysis of zygomatic form asymmetry revealed an average of 0.4 mm of surface deviation between hemifaces. The presence of such slight asymmetries in the zygoma warrants further investigation as to the clinical relevance of such skeletal asymmetries from both an esthetic and biomechanical consideration to provide insight as to the proper approach to zygomatic restoration in cases of zygomatic fracture.